2019
DOI: 10.1007/s42452-019-1520-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of bearing capacity of multiple strip footing on unreinforced and reinforced sand beds

Abstract: In this paper, the ultimate bearing capacity of multiple strip footings on reinforced and unreinforced sand beds is investigated using finite element method. The study utilizes efficiency factor to assess the change in the ultimate bearing capacity due to footing interference. The impacts of angle of internal friction, clear footing spacing and number of reinforcement layers on the efficiency factor are presented and evaluated. In addition, the effect of dilatancy angle and stress distribution in soil-reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The backfill, reinforcement and soil-reinforcement interface are considered and simulated separately in the numerical models [10,14,18,42]. In the literature, the finite element software for modeling reinforced foundation is PLAXIS 2D or 3D [13,[15][16][17]. In the models, the geogrid or plate structural element is generally used to simulate the reinforcement and the behavior of structural elements is modeled as linear-elastic material.…”
Section: Finite Element and Finite Difference Modellingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The backfill, reinforcement and soil-reinforcement interface are considered and simulated separately in the numerical models [10,14,18,42]. In the literature, the finite element software for modeling reinforced foundation is PLAXIS 2D or 3D [13,[15][16][17]. In the models, the geogrid or plate structural element is generally used to simulate the reinforcement and the behavior of structural elements is modeled as linear-elastic material.…”
Section: Finite Element and Finite Difference Modellingsmentioning
confidence: 99%
“…Hussein and Meguid [79] Finite element ABAQUS 3D Square Geogrid Badakhshan and Noorzad [59] Finite element ABAQUS 3D Circular, Square Geotextile Lai and Yang [80] Finite difference FLAC 2D Strip Geotextile Nasr and Azzam [60] Finite element PLAXIS 2D Strip Geogrid, Geotextile Oliaei and Kouzegaran [19] Finite difference FLAC 3D Square Planar geosynthetic, Geocell Venkateswarlu et al [20] Finite difference FLAC 3D Square Geogrid, Geocell Gao and Meguid [23] Discrete element PFC 3D Square Geogrid Ouria and Mahmoudi [81] Finite element -Strip Geotextile Aria et al [82] Finite element PLAXIS 3D Strip Wraparound geotextile Zidan and Mohamed [17] Finite element PLAXIS 2D Strip Geogrid Wang et al [24] Discrete element PFC 2D Strip Geogrid…”
Section: Pfc 2d Strip Geogridmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of investigators [21,22] remarked that geocell confinement in soil induces apparent cohesion, whereas the reinforcement depth is replaced by an equivalent layer, with homogenous properties [33]. The induced cohesion in the soil is related to the increase in the confining pressure on the soil due to the geocell reinforcement, which is calculated through the following equation:…”
Section: Parametric Calculations Of Reinforced Soil Propertiesmentioning
confidence: 99%
“…Several reports are published after the pioneering work reported by Stuart [1] using different analytical/numerical methods and experimental observations. The studies offering the understanding of two or multiple interfering footings using analytical/numerical methods use upper and lower bound limit analysis [2][3][4][5][6][7], finite difference method [8][9][10], finite element method [11][12][13][14][15][16][17][18] and analytical method [19,20], the probabilistic method [21] and others [22]. Then several experimental studies [23][24][25][26][27][28][29] have been reported on the interference of surface footings.…”
Section: Introductionmentioning
confidence: 99%